Communication Strategy of the Public Broadcasting Institution (LPP RRI) Lhokseumawe in Implementing the RRI Digital Application - Faridah Hannum; Bobby, Rahman; Cut, Andyna (CONTENT: Journal of Communication Studies, 2025)
This study examines the communication strategies employed by the Public Broadcasting Institution (LPP RRI) Lhokseumawe in implementing the RRI Digital application as part of its adaptation to technological developments in the digital era. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation, and documentation involving RRI management, staff, and active listeners. The findings reveal that internal strategies encompass employee training and application familiarization, whereas external strategies include cross-platform promotion, collaboration with local media, and optimization of social media channels. However, several challenges remain, including uneven digital literacy, infrastructure limitations, and the need for human resources to adapt to new technologies. The study recommends strengthening digital literacy initiatives, enhancing promotional strategies, and improving localized engagement efforts to increase public access and optimize the use of the RRI Digital application.